2001
DOI: 10.1037/0278-6133.20.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Projection in surrogate decisions about life-sustaining medical treatments.

Abstract: To honor the wishes of an incapacitated patient, surrogate decision makers must predict the treatment decisions patients would make for themselves if able. Social psychological research, however, suggests that surrogates' own treatment preferences may influence their predictions of others' preferences. In 2 studies (1 involving 60 college student surrogates and a parent, the other involving 361 elderly outpatients and their chosen surrogate decision maker), surrogates predicted whether a close other would want… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(185 citation statements)
references
References 40 publications
(63 reference statements)
8
175
0
1
Order By: Relevance
“…17,18,21,[25][26][27][28][29][30][31][32] In such studies, individuals are asked what they would want for themselves in particular circumstances. Their loved ones or designated proxies are then asked to predict what the patient would have wanted.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…17,18,21,[25][26][27][28][29][30][31][32] In such studies, individuals are asked what they would want for themselves in particular circumstances. Their loved ones or designated proxies are then asked to predict what the patient would have wanted.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…From yet another study, Lerouge and Warlop (2006) concluded that student couples had rather low prediction accuracy when forecasting their partner's bedroom furniture preferences. Fagerlin, Ditto, Danks, Houts, and Smucker (2001) reported that adult children's forecasts of whether their parents would want life-sustaining medical treatment were between 64% and 72% accurate across scenarios. As there were only two alternatives to choose from, chance level was 50%.…”
Section: Prediction Accuracymentioning
confidence: 99%
“…A review of the 16 studies of surrogate accuracy published between 1966 and 2005 found that overall, surrogates responding to a hypothetical decisionmaking scenario were inaccurate 32 percent of the time (Shalowitz, Garrett-Mayer, and Wendler 2006). Surrogates often presume (erroneously) that the patient's preferences are identical to their own: Surrogates' own preferences account for more of the variance in their decisions than do the patients' actual preferences (Bar-Tal, Barnoy, and Zisser 2005;Fagerlin et al 2001;Pruchno et al 2005).…”
mentioning
confidence: 99%